Burden or Relief? Fiscal Impacts of Recent Ukrainian Migration to Poland - Pawel Kaczmarczyk (Institute for the Study of Labor (IZA), 2015)
Immigration has become recently one of the most important subjects in socio-economic debates. In many countries immigrants are commonly presented as a threat to host economies and societies. On top of this fiscal impacts of immigration are ones of the hottest and most controversial topics in recent debate on migration. Against this background this paper aims at (1) discussing and synthesizing both theoretical and empirical literature on fiscal impacts of immigration, and (2) assessing empirically net fiscal position of Ukrainian immigrants in Poland. On the theoretical level we show that there exists no clear or coherent theoretical framework to explain fiscal effects of migration. Outcomes of empirical studies are mixed and not unequivocal, but generally prove that fiscal impacts of immigration are small or negligible. In terms of explanation, type of migration, labor market incorporation (absorption) and institutional framework at destination (structure of the welfare state) are presented as critical factors. Importance of those factors is clearly supported by empirical analysis presented. Net fiscal position of Ukrainian immigrants in Poland is unequivocally positive (and more beneficial than it is in case of the natives). This is mostly due to favorable characteristics of incoming immigrants (in terms of age and education) and particular migration strategies in work (pure labor migration). These features, however, to a large extent result from modes of labor market incorporation and structural characteristics of the Polish welfare state.
Keywords: F22; H55; H61; J11; J61; J68; 330; immigration to Poland; Ukrainian migration; welfare impacts of migration; net fiscal position